Peran Guru sebagai Penuntun dalam Mengembangkan Kreativitas Siswa Ditinjau dari Perspektif Kristen Alkitabiah - Ambarita, Polin Parulian; Irawati, Wahyu (Institut Agama Kristen Negeri Toraja, 2024)
Creativity is an essential skill needed to present solutions to problems in various areas of life. The need for creativity in the 21st century is a driving force for education to take a holistic approach in supporting the development of students' creativity starting in the school environment. According to a Biblical Christian perspective, creativity must be developed because every gift from God must be accounted for for His glory. The low level of student creativity in Indonesia in the learning process is a call for education to be improved. Optimizing the teacher's role as a guide is expected to be a solution to the problem of low student creativity. The aim of this research is to examine the role of teachers as guides in developing student creativity from a Biblical Christian perspective. The method used is a literature review. The role of the teacher as a guide will provide learning that is based on recognizing students' self-capacity as individuals who have creativity. Teachers as guides can guide the development of students' creativity by creating a creative classroom atmosphere in terms of learning models and activities. Based on this study, it can be concluded that the teacher's role as a guide can be a solution to students' low creativity. The suggestion given is for teachers to implement learning models that allow students to develop their creative abilities.